2013
DOI: 10.4236/jfcmv.2013.12008
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Tracer Point Method to Evaluate Turbulent Diffusion in Circular Pipe Flow

Abstract: Diffusion of a solute in turbulent flows through a circular pipe or tunnel is an important aspect of environmental safety. In this study, the diffusion coefficient of turbulent flow in circular pipe has been simulated by the Discrete Tracer Point Method (DTPM). The DTPM is a Lagrangian numerical method by a number of imaginary point displacement which satisfy turbulent mixing by velocity fluctuations, Reynolds stress, average velocity profile and a turbulent stochastic model. Numerical simulation results of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…During 2 s and 2.5 s, more fertilizer moved to the Y1 position, and it presented a gradient distribution on the radial section. This results were kept consistent with a finding proposed by Widiatmojo et al [22], who investigated the diffusion of a solute in turbulent flows through a circular pipe. Duda et al [23] also reported that the concentration showed a gradient distribution when the polymer diffused in the solvent.…”
Section: Fertilizer-water Mixing State In the Pipes At Different Posi...supporting
confidence: 93%
“…During 2 s and 2.5 s, more fertilizer moved to the Y1 position, and it presented a gradient distribution on the radial section. This results were kept consistent with a finding proposed by Widiatmojo et al [22], who investigated the diffusion of a solute in turbulent flows through a circular pipe. Duda et al [23] also reported that the concentration showed a gradient distribution when the polymer diffused in the solvent.…”
Section: Fertilizer-water Mixing State In the Pipes At Different Posi...supporting
confidence: 93%
“…The remaining relations necessary to calculate the density and viscosity at the interface between two fluids are expressed in Eqs. 9–14 8, 27, 29. In this study, the turbulent Schmidt number Sc t is considered to be 1 30, 31: true normalDnormalt = υnormalt S cnormalt true normalDnormalm = υnormalm Sc trueD= Dnormalm + normalDnormalt true CnormalA + CnormalB =1 true ρnormalm = CnormalA ρnormalA + CnormalB ρnormalB trueln υnormalm = CnormalA ln υnormalA + CnormalB ln υnormalB …”
Section: Mathematical Modelingmentioning
confidence: 99%